The analysis of expenses of a regional budget incidental to providing oncologic patients with narcotic analgesics during the out-patient period of treatment (on the example of Nizhny Novgorod region) - M. N. Lebedeva; S. . Kononova (Кубанский научный медицинский вестник, 2016)
This article presents the analysis of narcotic analgesics (NA) cost for the treatment of chronic pain syndrome (CPS) in oncologic patients, paid for with the funds of regional budget of the Nizhny Novgorod region in 2010-2014. The analysis was performed using the electronic prescriptions database. In total, during the abovementioned period, 2543 NA prescriptions, free of charge for patients with malignant neoplasm (MN), were issued from the regional budget. The yearly cost of providing oncologic outpatients with NA averaged 1,011,421.07 rubles for the regional budget. Most of that had been spent on trimeperidine (34.82%). It was noted that the expenses on transdermal fentanyl had increased. A cost of a single NA prescription for MN patients - beneficiaries of regional authorities - averaged 257.03 rubles.